Pengaruh Kesadaran Wajib Pajak, Sanksi Perpajakan, E-Filing, dan Tax Amnesty Terhadap Kepatuhan Pelaporan Wajib Pajak - Dewi, Santi Krisna; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2018)
The aims of the current study are to determine the effect of taxpayer awareness, tax sanctions, the application of e-filing system, and the knowledge about tax amnesty on the personal taxpayer reporting compliance in the East Denpasar Tax Office. The population of this study was conducted on personal taxpayer registered in the East Denpasar Tax Office. Non probability sampling method and purposive sampling technique were applied to determine the samples. The numbers of samples used were 100 respondents calculated using Slovin formula. The data were collected by questionnaire measured by likert scale. The result of the current study shows that taxpayer awareness, tax sanctions, the application of e-filing system, and the knowledge about tax amnesty have a positive and significant impact on the personal taxpayer reporting compliance in the East Denpasar Tax Office. Keyword: Taxpayer, e-filing, tax amnesty, taxpayer compliance